2010
DOI: 10.1016/j.physbeh.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence of two stressors on steadiness during index finger abduction

Abstract: Although several stressors have been used to examine the influence of arousal on motor performance, including noxious electrical stimulation, cold pressor test, and mental math calculations, no study has compared the influence of different physical stressors on motor output. The purpose of the study was to compare the influence of two stressors (cold pressor test and electrical stimulation) on the steadiness of the abduction force exerted by the index finger. Sixteen subjects (22.8 ± 3.5 yrs, 8 women) performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…This may have occurred because the handgrip manipulation was not strong enough to induce changes in LC activation (and consequences in brain states and dynamics) large enough to be detected via fMRI. Future studies may wish to employ a more aggressive manipulation, such as subjects dipping their hand in cold water, administering electrical pulses, or presenting jarring sounds (Marmon & Enoka, 2010; Oyarzún et al, 2012; Redondo et al, 2008; Schwabe & Schächinger, 2018; Stark et al, 2006). It is also possible that we would see stronger results in older adults, as neuromelanin accrues with age and peaks between ages 50-60 (Ma et al, 1999; Manaye et al, 1995; Zecca et al, 2004), or in a diseased population (i.e., subjects with Parkinson’s or Alzheimer’s diseases).…”
Section: Resultsmentioning
confidence: 99%
“…This may have occurred because the handgrip manipulation was not strong enough to induce changes in LC activation (and consequences in brain states and dynamics) large enough to be detected via fMRI. Future studies may wish to employ a more aggressive manipulation, such as subjects dipping their hand in cold water, administering electrical pulses, or presenting jarring sounds (Marmon & Enoka, 2010; Oyarzún et al, 2012; Redondo et al, 2008; Schwabe & Schächinger, 2018; Stark et al, 2006). It is also possible that we would see stronger results in older adults, as neuromelanin accrues with age and peaks between ages 50-60 (Ma et al, 1999; Manaye et al, 1995; Zecca et al, 2004), or in a diseased population (i.e., subjects with Parkinson’s or Alzheimer’s diseases).…”
Section: Resultsmentioning
confidence: 99%
“…The association between force steadiness and visual feedback is underscored by previous research that observed significant reductions in force fluctuations in the absence of visual feedback. Conversely, the introduction of visual feedback was associated with increased force fluctuations (Marmon and Enoka, 2010). Therefore, differences in the visual demands associated with both the one-and two-joint tests influence the modulation of motor unit discharge rates.…”
Section: Chapter IV -Discussionmentioning
confidence: 98%
“…This results in a phenomenon called common drive, or the simultaneous fluctuation of discharge rates among multiple motor units (DeLuca et al 1982). Common drive is ultimately responsible for force fluctuations during constant-force contractions, and can be influenced by the visual demands of the task, type of muscle contraction, properties of the motor units recruited, and the physical activity level of the individual (Enoka et al, 2003;Negro et al, 2009;Marmon and Enoka, 2010).…”
Section: Introductionmentioning
confidence: 99%